Analisis Program Speak Up Melalui Metode SERVQUAL di RSUD Aji Muhammad Parikesit Teggarong - Caroline, Audy Nabilla; Nurhasanah, Nurhasanah; Purwaningsih, Erwin (Lembaga Dongan Dosen, 2024)
Hospitals must be able to manage all their resources effectively to provide high-quality care and reduce the number of patient complaints related to the services that have been provided. Based on data on the number of patient complaints at RSUD A.M Parikesit Tenggarong that entered in 2020 - 2023, there were 88 complaints in the Speak Up program. Complaints using Speak Up can be made anywhere as it can be accessed through gadgets. Unfortunately, some patients have not been able to utilize the Speak Up program or understand the purpose of the Speak Up program. Therefore, the hospital wanted to know the user success of the Speak Up program which was able to facilitate patient complaints. This study uses a quantitative method with a cross-sectional approach with the aim of seeing user satisfaction with the Speak Up program at RSUD A.M Parikesit Tenggarong. The analysis was conducted to see the effect of independent variables (empathy, persuasion, impact, communication) on the dependent varial (Speak Up Program Satisfaction). The sample used in this study was 30 samples. The research instrument used for data collection is a questionnaire using a Likert scale. Also, the analysis carried out is univariate analysis and bivariate analysis which is processed with computer applications. Based on the results of the fisher test, the results show that there is a significant Based on the results of the fisher test, the results show that there is a relationship between empathy (0.001), persuasion, (0.003), impact (0.001), on speak up satisfaction.While there is no relationship between communication and speak up satisfaction (0.225) at RSUD A.M Parikesit Tenggarong.In this study, it is recommended that RSUD A.M Parikesit to better facilitate complaint users, provide two-way communication, and add a tracking feature in the Speak Up program to find out complaints that have been received, responded to, and resolved.